Hepatitis C virus infection and non‐hepatocellular malignancies in the DAA era: A systematic review and meta‐analysis. (8th May 2019) - Masarone, Mario; Persico, Marcello
Abstract: Background and Aims: Direct antiviral agents have greatly improved therapeutic options for chronic hepatitis C. Indeed, former "difficult‐to‐treat" patients can now be treated and can achieve sustained response. Hepatitis C virus (HCV) is associated with hepatocellular carcinoma and with B‐cell non‐Hodgkin lymphoma (B‐NHL). Other malignancies have been reported to be associated with HCV infection albeit with various grades of evidence. Antineoplastic treatment is often reduced or suspended in HCV‐positive cancer patients to avoid "HCV reactivation." In this setting, antiviral therapy combined with antineoplastic protocols may improve the outcome. For this reason, we conducted a systematic review and a meta‐analysis to update the association between HCV infection and non‐hepatocellular malignancies, and to shed light on the effects exerted by antiviral treatment on the natural history of oncological diseases. Methods: Relevant studies were identified by searching PUBMED, EMBASE and MEDLINE up to 1 August 2018. Pooled risk estimates were calculated with random‐effects models according to PRISMA guidelines. Results: A total of 58 studies were included in the analysis: 27 studies of the association between HCV and B‐NHL(OR 3.36; 95% CI 2.40‐4.72; P  < 0.00001);13 studies of the association between sustained virological response and progression‐free survival (PFS) in B‐NHL patients(OR 9.34; 95% CI 4.90‐17.79; P  < 0.00001); 13 studies of the association between HCV and intrahepatic‐cholangio‐carcinoma (OR 3.95;95% CI 2.25‐6.94; P  < 0.00001); and 5 studies of the association between HCV infection and pancreatic adeno‐carcinoma(OR 1.60; 95% CI:1.25‐2.04; P  = 0.0002). Conclusions: This study updates the strong association between B‐NHL and HCV infection, confirms the association between HCV and non‐hepatocellular tumours, and demonstrates a very strong association between viral eradication and a better outcome of HCV‐positive B‐NHL.